STRATEGI EFEKTIF PENGENDALIAN PERSEDIAAN BARANG JADI DALAM BISNIS MOCHI AO DAIFUKU: MENINGKATKAN EFISIENSI DAN KELAYAKAN OPERASIONAL - Anggita Vira Yunita; Arfie Laillya Azrawanda Putri; Yana Sulistyowati (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
The food industry is currently experiencing rapid growth due to the emergence of new and innovative food products. One such example is the "Ao Daifuku" or blue mochi business, which draws inspiration from Japanese cherry blossoms. This study aims to explore the implementation of inventory planning and control in the "Ao Daifuku" mochi business, including stock preparation, handling and sales progress, and reporting on remaining raw materials and physical goods. The objective of this research is to determine the effectiveness of planning and controlling finished goods inventory in improving operational efficiency and business feasibility. By conducting thorough field observations and practical analysis, the author examines the specific measures taken by the Ao Daifuku mochi business in managing finished product stocks, production processes, and distribution. These findings offer valuable insights into how an integrated inventory control strategy can enhance operational efficiency, optimize product availability, and strengthen Ao Daifuku's position in the culinary industry.